Experimental investigation of the effects of SnO2 nanoparticles and KCl salt on a water base drilling fluid properties. (5th August 2016) - Parizad, Amirhossein; Shahbazi, Khalil
Abstract: Reduction of proven gas and oil reserves and increasing demand for energy forces the petroleum industry to drill deeper and more complicated wells. Drilling in these harsh environments requires drilling fluids with specific characteristics. So, improvement of the drilling fluids that can act as proper fluids at high pressure and high temperature conditions is vital in the drilling industry. The purpose of this study is examining the effects of SnO2 nanoparticles on the properties of drilling fluids and determining of the extent of improvement of water‐based drilling fluids performance. These nanoparticles were added to polymeric water‐based drilling fluids in various concentrations of 1, 2.5, 5, and 7.5 g/L in the presence of KCl at concentrations of 5, 15, 30, 60, and 100 g/L. The experiments were done at temperatures of 30, 50, 70, and 90 °C. Electrical conductivity, thermal conductivity, and thixotropy of the resulting drilling fluids were investigated. Moreover, filtration of the drilling fluids at room temperature, 65, and 95 °C and pressures of 0.6895 MPa (100 psig) and 2.758 MPa (400 psig) and various nanoparticle concentrations were studied. It was found that electrical conductivity and thermal conductivity were increased by 30 % and 15 %, respectively. Finally, in order to have more accurate hydraulic calculations, five rheological models were studied and compared together. It was observed that the Herschel‐Bulkley‐Papanastasiou model showed the highest accuracy with an absolute relative error of 1.1 %.